'We've Got Some Underground Business Selling Junk Food': Qualitative Evidence of the Unintended Effects of English School Food Policies. (June 2014) - Fletcher, Adam; Jamal, Farah; Fitzgerald-Yau, Natasha; Bonell, Chris
Drawing on two qualitative studies, we report evidence of pervasive black markets in confectionery, 'junk' food and energy drinks in English secondary schools. Data were collected at six schools through focus groups and interviews with students ( n = 149) and staff ( n = 36), and direct observations. Supermarkets, new technologies and teachers' narrow focus on attainment have enabled these 'underground businesses' to emerge following increased state regulation of school food and drink provision. These activities represent a new form of counter-school resistance to institutional constraints within the context of enduring, although less visible, class-based stratification in British secondary schools. These black markets also appear to be partly driven by the unsafe and unsociable nature of school canteens, which was a recurring theme across all schools. These findings highlight how new school food 'bans' ignore the complex, ecological drivers of poor diet in youth and the potential for iatrogenic effects which exacerbate health inequalities.